Late-Onset Epilepsy and Occult Cerebrovascular Disease. Issue 4 (April 2014) - Gibson, Lorna M; Hanby, Martha F; Al-Bachari, Sarah M; Parkes, Laura M; Allan, Stuart M; Emsley, Hedley CA
The interface between cerebrovascular disease (CVD) and epilepsy is complex and multifaceted. Late-onset epilepsy (LOE) is increasingly common and is often attributed to CVD, and is indeed associated with an increased risk of stroke. This relationship is easily recognizable where there is a history of stroke, particularly involving the cerebral cortex. However, the relationship with otherwise occult, subcortical CVD is currently less well established yet causality is often invoked. In this review, we consider the diagnosis of LOE in clinical practice—including its behaviour as a potential mimic of acute ischemic stroke and transient ischemic attack; evidence for an association between occult CVD and LOE; and potential mechanisms of epileptogenesis in occult CVD, including potential interrelationships between disordered cerebral metabolism and perfusion, disrupted neurovascular unit integrity, blood–brain barrier dysfunction, and inflammation. We also discuss recently recognized issues concerning antiepileptic drug treatment and vascular risk and consider a variety of less common CVD entities associated with seizures.